Protocol for the UK cohort study to investigate the prevention of parastomal hernia (the CIPHER study). (2nd April 2021) - Tabusa, Hana; Blazeby, Jane M.; Blencowe, Natalie; Callaway, Mark; Daniels, Ian R.; Gunning, Amanda; Hollingworth, William; McNair, Augus G.; Murkin, Charlotte; Pinkney, Thomas D.; Rogers, Chris A.; Smart, Neil J.; et al.
Abstract: Aim: Abdominal surgery sometimes necessitates the creation of a stoma, which can cause future complications including parastomal hernia (PSH), an incisional hernia adjacent to and related to the stoma. PSH affects approximately 40% of patients within 2 years of stoma formation. Complications of PSH reduce a patient's quality of life and can be severe (e.g. bowel obstruction). PSHs are difficult to manage and can recur after surgical repair. Therefore, it is very important to prevent a PSH. Surgeons create stomas in different ways and both patient and surgical factors are believed to influence the development of PSH. The aim of the CIPHER study is to investigate the influence of different surgical techniques on the development of PSH. Method: The UK cohort study to investigate the prevention of parastomal hernia (the CIPHER study) aims to recruit 4000 patients undergoing elective or expedited surgery with the intention of forming an ileostomy or colostomy, irrespective of the primary indication for the planned surgery. For each patient, surgeons will describe their methods of trephine formation, mesh reinforcement of the stoma trephine, use of the stoma as a specimen extraction site and wound closure. The primary outcome will be incident PSH during follow‐up, defined as symptoms of PSH (custom‐designed questionnaire) and anatomical PSH, ascertained by independent reading of usual care CT scans. Secondary outcomes will include surgical site infection, the Comprehensive Complication Index, quality of life (EQ‐5D‐5L and SF‐12), PSH repair and use of NHS resources. Results: Results of the study will be submitted for publication in peer‐reviewed journals. All publications relating to the results of CIPHER will use a corporate authorship, 'The CIPHER Study Investigators' with named writing committee members. Conclusion: The CIPHER study will be the first to investigate detailed surgical methods of stoma formation in a large, representative cohort of patients with a range of primary indications, both cancer and noncancer.